1997
DOI: 10.1149/1.1837365
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Protection of Copper by a Self‐Assembled Monolayer of Alkanethiol

Abstract: A self-assembled monolayer of 1-dodecanethiol (DT) was formed on a copper surface pretreated using different methods. The corrosion protection abilities of the monolayer were evaluated in an air-saturated 0.51 M NaC1 solution using various techniques including electrochemical impedance spectroscopy, polarization, coulometry; weight loss, and x-ray photoelectron spectroscopy. It was found that the corrosion resistance of the monolayer was improved markedly by using a nitric acid etching method. A minimum concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
137
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(143 citation statements)
references
References 3 publications
2
137
0
Order By: Relevance
“…The mechanism by which the monolayer preserves solderability is thought to originate from these oxygen barrier properties, preventing the formation of surface oxides that hinder solder wetting. The reduction in surface oxidation rate has been demonstrated in earlier studies [2][3][4]. Furthermore, it has been shown that the barrier properties can be enhanced through the use of longer chain molecules that increase the van der Waals interactions and provide a thicker coating [5].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The mechanism by which the monolayer preserves solderability is thought to originate from these oxygen barrier properties, preventing the formation of surface oxides that hinder solder wetting. The reduction in surface oxidation rate has been demonstrated in earlier studies [2][3][4]. Furthermore, it has been shown that the barrier properties can be enhanced through the use of longer chain molecules that increase the van der Waals interactions and provide a thicker coating [5].…”
Section: Introductionmentioning
confidence: 77%
“…This is because SAM coatings are sensitive to temperature: phase changes have been observed, the ordered alkane structure can melt and ultimately at a sufficiently high temperature the SAM molecules will desorb and decompose [6,7]. Indeed, to date it has been shown that temperature does effect barrier properties [2][3][4]. SAM coated copper surfaces stored in a freezer showed good fluxless solder wetting up to a few months after preparation, while at room temperature, solderability was only maintained for 24-48 hours.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of SAM coatings to reduce the surface oxidation rate of the substrate metal has been demonstrated in earlier studies [9]- [11] and is attributed to the densely packed pseudocrystalline arrangement of the alkanethiol chains that retards the diffusion of oxygen and other oxidizing species including water vapor, to the underlying copper substrate. It has also been shown that barrier properties improve with increasing alkanethiol chain length due to an increase in the van der Waals interactions and greater coating thickness [12].…”
Section: Introductionmentioning
confidence: 90%
“…Enormous corrosion inhibitors, nanofilms and coatings have been accordingly explored with different fabrication techniques for copper protection. One of the most effective approaches is to prepare selfassembled monolayer (SAM) of organic inhibitors on copper surface [2]. Thus, a series of organic inhibitive compounds have been investigated, such as benzotriazole [3], thiol, dithiol and dithiocarboxylic [4], silane [5], triazinedithiol [6].…”
Section: Introductionmentioning
confidence: 99%